A comparison of different methods for including 'age at menopause' in analyses of the association between hormone replacement therapy use and breast cancer. Issue 1 (1st January 2007) - Simpson, Julie A; English, Dallas R; MacInnis, Robert J; Giles, Graham G; Gertig, Dorota M; Hopper, John L
Abstract : Background and methodology: Late 'age at menopause' is a recognised risk factor for postmenopausal breast cancer and is also associated with decreased use of hormone replacement therapy (HRT). When investigating the association between HRT use and breast cancer risk it is therefore necessary to adjust for the potential confounder, 'age at menopause'. 'Age at menopause', however, cannot be determined for women with a hysterectomy and ovarian conservation. Using data on 13 357 postmenopausal women in whom 396 cases of invasive breast cancer were diagnosed during 9 years of follow-up from the Melbourne Collaborative Cohort Study, we compared the estimates of relative risk of HRT use for breast cancer for three different methods of dealing with missing data: complete-case analysis, single imputation and multiple imputation. Results: 'Age at menopause' was missing for 17% of the data. Both HRT use and 'age at menopause' were significant risk factors for breast cancer, although 'age at menopause' only marginally confounded the estimates of risk for HRT. Women with 'age at menopause' missing did not represent a random sample of the population. Complete-case analyses resulted in higher estimates of the risk associated with HRT use compared with the different methods of imputation. Discussion and conclusions: We recommend that analyses investigating the association between HRT and breast cancer should present the results in two ways: excluding women with 'age at menopause' missing and including the women using multiple imputation. For both methods, estimates of risk, with and without the adjustment of 'age at menopause', should be given.